MEDIA AND HUMAN CAPITAL DEVELOPMENT: CAN VIDEO GAME PLAYING MAKE YOU SMARTER? - Suziedelyte, Agne (Economic Inquiry, 2015)
ABSTRACT According to the literature, video game playing can improve such cognitive skills as problem solving, abstract reasoning, and spatial logic. I test this hypothesis using the data from the Child Development Supplement to the Panel Study of Income Dynamics. The endogeneity of video game playing is addressed by using panel data methods and controlling for an extensive list of child and family characteristics. To address the measurement error in video game playing, I instrument children's weekday time use with their weekend time use. After taking into account the endogeneity and measurement error, video game playing is found to positively affect children's problem solving ability. The effect of video game playing on problem solving ability is comparable to the effect of educational activities. ( JEL I2, J13, J24)